Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.19030/jabr.v8i1.6190
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Name Changes: The Association Between Functional Name Characteristics And Stock Performance

Abstract: A well-chosen corporate name communicates much information and emotion to a firms publics. Despite the tremendous costs involved in a corporate name change, many corporations change names when pursuing a new strategic direction. In this study, we examine the relationship between functional name characteristics and stock performance around name change announcements. The results show that distinctiveness is the most important explanatory variable of abnormal stock returns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…More specifically, the authors find a positive market response to the announcement of firm's adding “.com” to the current company name, with firms experiencing abnormal returns of approximately 53 percent for the 5 days following the announcement of a name change . Morris and Reyes () report that positive abnormal returns attributed to name changes are generally associated with name characteristics, where the “distinctiveness” of the name is the most important factor in explaining abnormal returns…”
Section: Corporate Name Change Literaturementioning
confidence: 99%
“…More specifically, the authors find a positive market response to the announcement of firm's adding “.com” to the current company name, with firms experiencing abnormal returns of approximately 53 percent for the 5 days following the announcement of a name change . Morris and Reyes () report that positive abnormal returns attributed to name changes are generally associated with name characteristics, where the “distinctiveness” of the name is the most important factor in explaining abnormal returns…”
Section: Corporate Name Change Literaturementioning
confidence: 99%
“…The few studies that have looked at the effect of the change itself were either restricted to smaller non-US stock exchanges or imposed a variety of restrictions on the types of names studied. Morris & Reyes (1992) studied corporate name changes based on functional name characteristics such as distinctiveness and memorability. They find a statistically significant positive response among inexperienced investors to names improved by this criterion.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Howe (1982) claimed that the company's name is one of its public images and a poor choice of name may be an obstacle for the firm to overcome, while a clever, such as amusing and informative, name may have a positive influence on individuals' perceptions of the company. Morris and Reyes (2011) argued that a well-chosen corporate name communicates much information and emotion to the firm's public. Green and Jame (2013) found that companies with short and easy to pronounce names have a higher breadth of ownership, greater share turnover, lower transaction price impacts, and higher valuation ratios.…”
Section: Introductionmentioning
confidence: 99%